The Effect of Sales Growth and Inflation Rate on Profit Changes in Food and Beverage Sub-Sector Manufacturing Companies Listed on The Indonesia Stock Exchange - Dini Fauziyah Utomo; Cepi Pahlevi; Fauzi R. Rahim (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This study aims to determine and analyze the effect of sales growth and the inflation rate on profit changes in food and beverage sub-sector manufacturing companies listed on the Indonesian stock exchange in the 2018-2020 period. Data collection uses secondary data obtained from financial reports accessed through www.idx.co.id and data on food and beverage company stocks, purposive sampling technique used. The population is 26 food and beverage companies listed on the Indonesia Stock Exchange for the 2018-2020 period, with 42 observations. While the samples taken amounted to 14 observations. The results of the research variable data have been tested on the classical assumptions in the form of normality assumptions, multicollinearity assumptions, and heteroscedasticity assumptions. After collecting the data, the data analysis method used multiple linear regression techniques and tested the hypothesis. The data was analyzed using the SPSS (Statistic et al.) Version 26 program. The results showed that sales growth had a positive and significant effect on changes in profits, and the inflation rate had a significant negative effect on changes in profits.